OCTN2-mediated acetyl-l-carnitine transport in human pulmonary epithelial cells in vitro - Salomon, Johanna J. (Pharmaceutics, 2019)
The carnitine transporter OCTN2 is associated with asthma and other inflammatory diseases. The aims of this work were (i) to determine carnitine uptake into freshly isolated human alveolar type I (ATI)-like epithelial cells in primary culture, (ii) to compare the kinetics of carnitine uptake between respiratory epithelial in vitro cell models, and (iii) to establish whether any cell line was a suitable model for studies of carnitine transport at the air-blood barrier. Levels of time-dependent [3H]-acetyl-l-carnitine uptake were similar in ATI-like, NCl-H441, and Calu-3 epithelial cells, whereas uptake into A549 cells was ~5 times higher. Uptake inhibition was more pronounced by OCTN2 modulators, such as l-Carnitine and verapamil, in ATI-like primary epithelial cells compared to NCl-H441 and Calu-3 epithelial cells. Our findings suggest that OCTN2 is involved in the cellular uptake of acetyl-l-carnitine at the alveolar epithelium and that none of the tested cell lines are optimal surrogates for primary cells.